PERANCANGAN APLIKASI BELAJAR BAHASA ARAB BERBASIS ANDROID MENGGUNAKAN ANDROID STUDIO - Ely Nuryani; Darpi Darpi; Ahmad Muhtapid (Journal of Innovation And Future Technology (IFTECH), 2019)
Development of technology in this era is now increasingly rapid, thus triggering humans to enter a new era in life known as E-Life (Electronic life), which means that in this life has been influenced by various needs electronically. At present there are increasingly widespread activities that have been based on electronic devices to support human needs such as e-commerce, e-library, e-government, e-journal, e-medicine, e-laboratory, e-learning and other things related to devices electronic. Because this is an early age Arabic language teaching must be done to prepare themselves to compete in the current era of globalization. but in terms of teaching Arabic to early childhood there are obstacles, namely children sometimes get bored and lazy when learning Arabic. The design of this application is based on Android mobile to facilitate learning. The purpose of designing this application so that children are not bored learning English and have an interest in learning Arabic, in addition to directing the habit of children playing into children more like learning Arabic.